Optimal reactive power dispatch using stochastic chance-constrained programming - López, Julio C. [UNESP]; Muñoz, José I.; Contreras, Javier; Mantovani, J. R. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Deterministic Optimal Reactive Power Dispatch problem has been extensively studied, such that the demand power and the availability of shunt reactive power compensators are known and fixed. Give this background, a two-stage stochastic optimization model is first formulated under the presumption that the load demand can be modeled as specified random parameters. A second stochastic chance-constrained model is presented considering uncertainty on the demand and the equivalent availability of shunt reactive power compensators. Simulations on six-bus and 30-bus test systems are used to illustrate the validity and essential features of the proposed models. This simulations shows that the proposed models can prevent to the power system operator about of the deficit of reactive power in the power system and suggest that shunt reactive sourses must be dispatched against the unavailability of any reactive source. © 2012 IEEE.
Keywords: Chance constraint; optimal reactive power dispatch; stochastic programming; two-stage; uncertainty; Chance-constrained model; Chance-constrained programming; Load demand; Optimal reactive power dispatch; Power system operators; Random parameters; Reactive power compensator; Reactive sources; Stochastic optimization model; Test systems; Computer programming; Computer simulation; Exhibitions; Optimization; Stochastic models; Stochastic programming; Stochastic systems; Reactive power